Use of statins and the risk of dementia and mild cognitive impairment: A systematic review and meta-analysis - Chu, Che-Sheng; Tseng, Ping-Tao; Stubbs, Brendon; Chen, Tien-Yu; Tang, Chia-Hung; Li, Dian-Jeng; Yang, Wei-Cheng; Chen, Yen-Wen; Wu, Ching-Kuan; Veronese, Nicola; Carvalho, Andre F.; Fernandes, Brisa S.; et al. (Scientific reports, 2018)
We conducted a systematic review and meta-analysis to investigate whether the use of statins could be associated with the risk of all-caused dementia, Alzheimer’s disease (AD), vascular dementia (VaD), and mild cognitive impairment (MCI). Major electronic databases were searched until December 27 th , 2017 for studies investigating use of statins and incident cognitive decline in adults. Random-effects meta-analyses calculating relative risks (RRs) were conducted to synthesize effect sizes of individual studies. Twenty-five studies met eligibility criteria. Use of statins was significantly associated with a reduced risk of all-caused dementia (k = 16 studies, adjusted RR (aRR) = 0.849, 95% CI = 0.787–0.916, p = 0.000), AD (k = 14, aRR = 0.719, 95% CI = 0.576–0.899, p = 0.004), and MCI (k = 6, aRR = 0.737, 95% CI = 0.556–0.976, p = 0.033), but no meaningful effects on incident VaD (k = 3, aRR = 1.012, 95% CI = 0.620–1.652, p = 0.961). Subgroup analysis suggested that hydrophilic statins were associated with reduced risk of all-caused dementia (aRR = 0.877; CI = 0.818–0.940; p = 0.000) and possibly lower AD risk (aRR = 0.619; CI = 0.383–1.000; p = 0.050). Lipophilic statins were associated with reduced risk of AD (aRR = 0.639; CI = 0.449–0.908; p = 0.013) but not all-caused dementia (aRR = 0.738; CI = 0.475–1.146; p = 0.176). In conclusion, our meta-analysis suggests that the use of statins may reduce the risk of all-type dementia, AD, and MCI, but not of incident VaD.